Soil compaction management and soybean yields with cover crops under no-till and occasional chiseling - Calonego, Juliano C. [UNESP] (2017)
The introduction of cover crops in agricultural systems under no-till is important in soil structuring and remediation. However, there is a lack of studies exploring the effects of cover crops compared with other soil compaction control tools, such as chiseling, in the long term, mainly under tropical climates. This study aimed to evaluate soil physical properties by cover crops and chiseling in a compacted soil, as well as its effects on soybean yields. The experiment was conducted in Botucatu, Brazil, under no-till. Three crops were grown per year. Soybean [Glycine max (L.) Merrill] was cropped as summer crop in rotation with triticale (X Triticosecale Wittmack) or sunflower [Helianthus annuus (L.)] as fall/winter crop. In spring, three different cover crops were grown, pearl millet [Pennisetum glaucum (L.) R. Brown], forage sorghum [Sorghum bicolor (L.) Moench] and sunn hemp [Crotalaria juncea (L.)], compared to a fallow treatment, which was chiseled in 2003, 2009 and 2013 only, always in October and down to 0.60 m depth. The first chiseling increased soil macroporosity and soybean yields in the immediate cropping season (2003/2004). However, these benefits were short-lived and in two years the use of cover crops resulted in higher yields. In the long-term, cover crops improve soil structure, with equal or better results than those obtained by occasional chiseling, as an increase in soil macroporosity by sunn hemp up to 0.20 m depth and a decrease in soil bulk density by sunn hemp and pearl millet in the 0.40-0.60 m layer. Among the cover crops, sunn hemp is particularly interesting, because it increases macroporosity in clay soils otherwise with limited aeration and increases the soybean yield. (C) 2017 Published by Elsevier B.V.